Optimizing Decision-Making in Guidance and Counseling Programs: A Systematic Review of The CIPP Evaluation Model - Astha, Kadek Ayu Gayatri; Hidayah, Nur; Wahyuni, Fitri; Prabawa, Abi Fa’izzarahman (Suluh: Jurnal Bimbingan dan Konseling, 2026)
Aim: This study aims to examine the CIPP evaluation model as a decision-making tool in the development of Comprehensive Guidance and Counseling programs through a Systematic Literature Review (SLR) approach. The review was conducted on 12 reputable scientific articles selected based on the PRISMA protocol from a scholarly search engine, namely Google Scholar. Data analysis utilized thematic synthesis to systematically identify patterns of findings across studies. The results of the study addressed two main research questions. First, the CIPP model has been widely applied in various contexts of Guidance and Counseling (BK) programs within educational institutions, demonstrating the ability to comprehensively diagnose program conditions across all components: context, input, process, and product. Second, the CIPP model significantly contributes as a decision-making tool in Comprehensive Guidance and Counseling programs, both structurally in evaluating program aspects and strategically in supporting data-driven counselor accountability. These findings imply that the consistent application of the CIPP model can improve the quality of guidance and counseling services, strengthen counselors’ professional competencies, and provide an empirical foundation for educational policy-making oriented toward the optimal development of students.